Unilateral linear lichen Planus Along The Lines Of Blaschko - Thappa Devinder Mohan (Indian Journal of Dermatology, 2003)
Linear lichen planus is uncommon and only occasionally has a relationship with Blaschkoâ€s lines been observed. We describe herewith a patient who had this uncommon variant of linear lichen planus along with erosive lesion of lichen planus over the glans.